The material and immaterial connectivity underpinning Iran–Central Eurasia relations: elite discourse in Baku and Tashkent - Tomek, J (2023)
The collapse of the Soviet Union and the independence of the republics of the South Caucasus and Central Asia opened a window of geopolitical opportunity to the Islamic Republic of Iran. Like Turkey, Iran could henceforth start leveraging millennia-worth of ‘immaterial connectivity’: religious, linguistic, cultural and historical commonalities, hitherto impeded and obscured by decades of Soviet hegemony. Compared to Turkey, however, Iran has a clear advantage in terms of ‘material connectivity’, by virtue of directly bordering both sub-regions, as well as the Caspian Sea waterway. It has thus been able to court the bulk of its landlocked interlocutors with the promise of enabling access to international shipping routes via the Persian Gulf and the Gulf of Oman, as well as overland transport along east–west and north–south Eurasia-spanning axes respectively. With interlocutors such as Turkmenistan and Kazakhstan, the latter has been done without much compounding complexity, largely in pursuit of pragmatic interests, especially once it became clear that Iran’s northern policy vector is an overwhelmingly-de-ideologized pragmatic one. By contrast, the two most complex constituent dyads of the Iran–Central Eurasia regional nexus—namely the Tehran–Baku and the Tehran–Tashkent relationship, which are both explored here and compared in an in-depth manner—have been experiencing particular volatility over the course of the past three decades. Applying the theoretical framework of constructivism and relying on the methodological tool of analysing all hegemonic national discourse where Iran is the common denominator—discourse relayed over the course of elite interviews in Baku and Tashkent in the 2021–2022 period—one can discern some overarching trends. Firstly, in addition to Tehran systematically deferring to Moscow on Eurasian matters, the two aforementioned relationships have operated as a function of the broader Tehran–Baku–Yerevan and Tehran–Tashkent–Dushanbe ‘relationship triangles’ respectively. Assumptions of the latter’s perennial nature are refuted by a key finding that the latter dynamic had been limited to the Karimov era in Uzbekistan and is no longer operational. Secondly, Iran’s conspicuous post-Cold War cultural redeployment, occurring against the backdrop of proliferating material links in the area transport infrastructure, has been challenging elements of Azerbaijan’s and Uzbekistan’s still-consolidating nationbuilding narratives. Particularly in the former—Shia-Muslim-majority—case, strong cultural and historical proximity to Iran and shared legacies of Persianate elite culture has shown to hinder the development of closer regional ties, rather than being conducive to it.